2007
DOI: 10.1002/14651858.cd004572.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Aldose reductase inhibitors for the treatment of diabetic polyneuropathy

Abstract: We found no statistically significant difference between aldose reductase inhibitors and placebo in the treatment of diabetic polyneuropathy. Any future clinical trials of aldose reductase inhibitors should be restricted to compounds proven to have substantial biological or preclinical advantages over previously tested agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(88 citation statements)
references
References 42 publications
0
86
0
2
Order By: Relevance
“…Because of that study, many preclinical studies on various aldose reductase inhibitors that eventually resulted in large phases 2 and 3 clinical trials relied on reversal of conduction velocity changes as 1 of the primary outcome measures. Although it is unclear if reliance on nerve conduction velocity in preclinical models is the cause of failure of many aldose reductase inhibitors in clinical trials [25], it did likely play a role.…”
Section: Diabetic Neuropathymentioning
confidence: 99%
See 1 more Smart Citation
“…Because of that study, many preclinical studies on various aldose reductase inhibitors that eventually resulted in large phases 2 and 3 clinical trials relied on reversal of conduction velocity changes as 1 of the primary outcome measures. Although it is unclear if reliance on nerve conduction velocity in preclinical models is the cause of failure of many aldose reductase inhibitors in clinical trials [25], it did likely play a role.…”
Section: Diabetic Neuropathymentioning
confidence: 99%
“…Unfortunately, the literature is filled with failed clinical trials that relied on preclinical data using animal models that may not have been the most optimum models or outcome measures irrelevant to the underlying disease pathogenesis. A classical example of this issue is the use of small changes in nerve conduction velocity in diabetic animal models and multiple failed clinical trials with aldose reductase inhibitors [3]. This review will focus on 3 common diseases that cause peripheral neuropathy and outline the past, present, and future of animal models in the use of mechanistic studies and drug development.…”
Section: Introductionmentioning
confidence: 99%
“…However, ARI trials are still very much in the research area and, although there are some promising reports on improvement in symptoms and in some objective measures of neuropathy, the degree of benefit obtained has not been outstanding, and therefore, it is still too early to evaluate the role of ARIs in the management of diabetic neuropathy, especially in children and adolescents. A recent Cochrane review of ARIs, nevertheless, concluded that benefit has not been demonstrated from these agents (86).…”
Section: Secondary Interventionsmentioning
confidence: 99%
“…Unfortunately, AR inhibitors have fallen short. The problem is that AR inhibitors are very effective at preventing cataracts but they have been eliminated from any eye disease-related clinical trials because of adverse side effects (6). When diabetic patients were treated with the AR inhibitor sorbinil, enhancement of the nerve conduction velocity was observed (18), but generally, the effect had shown to be modest with major adverse reaction of hypersensitivity similar to that seen with other hydantoins.…”
Section: Discussionmentioning
confidence: 99%
“…While a number of structurally diverse compounds inhibit AR significantly, many of these compounds possess poor pharmacokinetic properties or side-effects not associated with the specific inhibition of AR (6). These side effects range from severe allergic reactions with sorbinil (7), impaired kidney function with zenarestat (8), to alteration of liver function with tolrestat (9).…”
Section: Introductionmentioning
confidence: 99%